2013
DOI: 10.1590/s1413-81232013000700023
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de um programa de aplicação de toxina botulínica tipo A em crianças do Vale do Jequitinhonha com paralisia cerebral

Abstract: O objetivo do estudo foi avaliar os efeitos de um programa público de aplicação de toxina botulínica tipo A (TBA) na espasticidade muscular, amplitude de movimento, qualidade da marcha, independência funcional e qualidade de vida de crianças e adolescentes com paralisia cerebral (PC). Foi realizado um estudo quase experimental que avaliou os efeitos do emprego da TBA, aplicada três vezes, com intervalos de três meses, em 14 crianças com PC. Estas foram avaliadas através da Escala Modificada de Ashworth, Goniom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…A melhoria no estado de saúde da criança, com diminuição de sequelas motoras e até mesmo da espasti-Tabela 1 -Correlações entre os valores médios dos domínios da escala CP Qol-Child, Fortaleza, 2013. (11) , resulta em maior habilidade no uso dos equipamentos que permitem locomoção e consequente socialização.…”
Section: Discussionunclassified
“…A melhoria no estado de saúde da criança, com diminuição de sequelas motoras e até mesmo da espasti-Tabela 1 -Correlações entre os valores médios dos domínios da escala CP Qol-Child, Fortaleza, 2013. (11) , resulta em maior habilidade no uso dos equipamentos que permitem locomoção e consequente socialização.…”
Section: Discussionunclassified
“…The results showed through PEDI that there was an improvement in ROM, influencing self-care and functional skills, but no decrease in caregiver assistance was observed. 24 The evaluation of the effects of Transcranial Direct-Current Stimulation (TDCS) applied on the primary motor cortex in children with CP showed that there was no significant improvement in the areas assessed by PEDI (self-care, mobility and social function) after the experiment. 25 Another study assessed, from the analysis of the PEDI results, changes in the functional use of the upper extremity in children undergoing the adapted Constraint-Induced Movement Therapy (CIMT) protocol, which consists of restricting the movement of the unaffected upper limb and providing intensive training in the affected limb.…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, the administration should be performed by medical specialists in physical medicine and rehabilitation (physiatry) and/or neurologists 106 affiliated with a multi-professional rehabilitation program. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the administration should be performed by medical specialists in physical medicine and rehabilitation (physiatry) and/or neurologists 106 affiliated with a multi-professional rehabilitation program. 50 The fact that 50.5% of articles lack information on adverse effects is extremely relevant, as such data is crucial for the clinical administration of BTX in terms of safety and effectiveness. There were reports of systemic adverse effects in 12.4% of clinical trials; however, no deaths were directly related to the administration of BTX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation